Primera cita de Opius (Opiothorax) inflammatus Fisher, 1963 (Hymenoptera, Braconidae), parasitando larvas de Liriomyza bryoniae (Kaltenbach, 1858) (Diptera, Agromyzidae) en España - M.ª Dolores Alcázar Alba; José Vicente Falcó; M.ª Mar Téllez; Lidia Lara; Mario Porcel; Estefanía Rodríguez (Boletín de la Asociación Española de Entomología)
First Record of Opius (Opiothorax) inflammatus Fisher, 1963 (Hymenoptera, Braconidae) as a parasitoid of Liriomyza bryoniae (Kaltenbach, 1858) (Diptera, Agromyzidae) in Spanish greenhouse crops